Using semantic technology to tame the data variety challenge - Horrocks, I; Giese, M; Kharlamov, E; Waaler, A (Institute of Electrical and Electronics Engineers, 2016)
Data analytics can be problematic in real-world settings, where data sources are often distributed, heterogeneous, and dynamic. Semantic technologies can now offer a practical solution that addresses scalability and usability issues, and has been successfully deployed in industry applications.